Peristiwa Tutur Upacara Pulang-Memulangkan Adat Melayu Sambas - Yupi Pahlufianti; Suhandano Suhandano (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2022)
The ceremony of pulang-memulangkan is a speech event which includes speech components, then by Dell Hymes it includes aspects of SPEAKING. This study applies aspects of SPEAKING in seeing speech event at the ceremony of pulang-memulangkan. This study observes at the oral discourse spoken by the participants of the ceremony pulang-memulangkan. By using qualitative methods, data was taken by applying two methods, namely the non-participant observation method by using the recording technique and the interview method. Through the object of research in the form of oral discourse spoken by the participants involved, seeing the cultural group of the Sambas Malay community, responding to a marriage through a discourse that was built in the ceremony of pulang-memulangkan. The results of the study indicate that the ceremony of pulang-memulangkan has included components in speech event. These components support the process of pulang-memulangkan ceremony discourse speech. So that the meaning and purpose interpreted through linguistic and non-linguistic aspects of pulang-memulangkan ceremony discourse can be interpreted well by participants and audiences.